2005
DOI: 10.1007/s10350-004-0891-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiotherapy Improves Outcome in Recurrent Rectal Cancer

Abstract: Preoperative radiotherapy for recurrent rectal cancer results in a higher number of complete resections and an improved local control compared with patients treated without radiotherapy. Preoperative radiotherapy should be standard treatment for patients with recurrent rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 45 publications
6
40
1
Order By: Relevance
“…Preoperative chemoradiation and intraoperative radiation may improve local control and survival in patients with locally recurrent disease with acceptable morbidity. Vermaas et al [35] reported that preoperative radiotherapy for recurrent rectal cancer results in a higher number of complete resections and improved local control in comparison to patients treated without radiotherapy. High-dose rate interstitial brachytherapy delivers high-dose, highly controlled and focused radiation to specific sites of disease, thereby minimizing the degree of injury to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chemoradiation and intraoperative radiation may improve local control and survival in patients with locally recurrent disease with acceptable morbidity. Vermaas et al [35] reported that preoperative radiotherapy for recurrent rectal cancer results in a higher number of complete resections and improved local control in comparison to patients treated without radiotherapy. High-dose rate interstitial brachytherapy delivers high-dose, highly controlled and focused radiation to specific sites of disease, thereby minimizing the degree of injury to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9]11,18,19,28,29,30,[33][34][35][36][37]41,44,46,47,[50][51][52][53]56,57 Without prior EBRT, the total dose was 40-60 Gy in most studies, with an overall range of 15-80 Gy. Conventional fractionation (1.8-2.0 Gy per fraction) was uniformly applied in 13 studies, 3,6,7,9,11,18,19,28,30,36,46,50,52 and selective use of a hypofractionated schedule (fractions of 5 Gy) was described in 2 studies. 34 described the use of re-EBRT, 7 of which specified the rate.…”
Section: Perioperative Treatment For Local Recurrencementioning
confidence: 99%
“…Thirteen studies 3,6,7,11,15,19,25,28,35,36,47,52,57 specified the total dose of IORT, which mostly ranged from 10 to 20 Gy.…”
Section: Researchmentioning
confidence: 99%
“…Local recurrence is a serious complication in the treatment of rectal cancer, since it causes disabling symptoms and is difficult to cure [1, 2]. Previous reports [3, 4 ]documented a high incidence of local recurrence up to 40% after conventional surgery. Heald et al[ 5] and Heald and Ryall [6 ]described a new concept in operative anatomy, the total mesorectal excision (TME) technique, in which the entire mesorectum is enveloped and resected.…”
Section: Introductionmentioning
confidence: 99%